Simulation Analysis of Voltage Distribution of 500kV Degraded Magnetic Insulator String. Issue 1 (December 2020) - Xueming, Zhou; Danhui, Hu; Zhiqiang, Feng; Ding, Zhou; Xiaopo, Mao
Abstract: Insulators are important power grid equipment and key components to ensure electrical insulation performance. Porcelain insulators with reduced insulation performance are generally low or zero, and are broken down under lightning overvoltage or even normal operating voltage. The thermal effect generated by the strong power frequency fault current flowing through the porcelain insulator will often cause deterioration of the porcelain insulator. The iron cap exploded, causing serious accidents such as stringing of insulators and grounding of wires. If there are continuous multiple pieces of zero-value insulators in the insulator string, the voltage of the insulators around the zero-value insulators will increase compared to normal conditions, and the normal insulators farther from the zero-value insulators will be less affected. If there are multiple consecutive zero-value insulators at different positions in the insulator string, if the number of zero-value insulators in the insulator string is large enough, and the distribution positions are more diffuse, the voltage of the entire string of insulators in the insulator string will be biased as a whole high.